Impact of diversiﬁcation and volatility in investment portfolios: Bolsa de Valores de Lima - Juli Chambilla, Dany Elias (2020)
The purpose was determining the eﬀect of diversiﬁcation and the eﬃcient frontier on the investment portfolio of Lima Stock Exchange in the las 4 years. The type of research carried out is quantitative and explanatory, based on the statistical information of the quotation on the Lima Stock Exchange in the period 2015-2019. The proﬁtability and the risk can be done through by the Excel and Excel Solver program and Eviews too. Of the 11 titles selected as sample of the Lima Stock Exchange (LSE), the expected return and volatility in the last of 4 years were calculated. The most eﬃcient portfolio set in the market was determined. Using the theory of diversiﬁcation, a contrast was obtained in the results, this is why the result of volatility is of the utmost importance for investors in the portfolio, since it contributes to the decrease in risk and the increase in proﬁtability.